Infection with Schistosoma mansoni has an Effect on Quality of Life, but not on Physical Fitness in Schoolchildren in Mwanza Region, North-Western Tanzania: A Cross-Sectional Study. - Safari Kinung'hi; Pascal Magnussen; Godfrey Kaatano; Annette Olsen (Public Library of Science (PLoS), 2016)
BACKGROUND:Infection with Schistosoma mansoni negatively impact children's physical health and may influence their general well-being. The aim of this study was to investigate the effect of S. mansoni infections on a panel of morbidity indicators with emphasis on quality of life (PedsQL; measured in four different dimensions) and physical fitness (measured as VO2 max) among 572 schoolchildren aged 7-8 years. METHODOLOGY/PRINCIPAL FINDINGS:Prevalence of S. mansoni infections was 58.7%, with an arithmetic mean (95% CI) among positives of 207.3 (169.2-245.4) eggs per gram (epg). Most infections were light (56.5%), while 16.4% had heavy infections. Girls had significantly higher arithmetic mean intensities (95% CI) than boys (247.4 (189.2-305.6) vs. 153.2 (110.6-195.8); P = 0.004). A total of 30.1% were anaemic with no sex difference. Stunting and wasting was found in less than 10% of the population. There was no association between S. mansoni prevalence or intensities and the following parameters: anthropometry, anaemia, liver or spleen pathology in neither univariable nor multivariable linear regression analyses. However, in univariable analyses children with S. mansoni infection had a significantly lower score in emotional PedsQL (95% CI) than uninfected (77.3 (74.5-80.1) vs. 82.7 (79.9-85.5); P = 0.033) and infected children had a higher VO2 max (95% CI) compared to uninfected (51.4 (51.0-51.8) vs. 50.8 (50.3-51.3); P = 0.042). In multivariable linear regression analyses, age, S. mansoni infection, haemoglobin and VO2 max were significant predictors for emotional PedsQL while significant predictors for VO2 max were physical PedsQL, height, age and haemoglobin. S. mansoni infection was thus not retained in the multivariable regression analyses on VO2 max. CONCLUSIONS/SIGNIFICANCE:Of the measured morbidity parameters, S. mansoni infection had a significant effect on the emotional dimension of quality of life, but not on physical fitness. If PedsQL should be a useful tool to measure schistosome related morbidity, more in depth studies are needed in order to refine the tool so it focuses more on aspects of quality of life that may be affected by schistosome infections.